Economic and life cycle assessments of biomass utilization for bioenergy products. (4th May 2017) - Liu, Weiguo; Wang, Jingxin; Richard, Tom L.; Hartley, Damon S.; Spatari, Sabrina; Volk, Timothy A.
Abstract: A modeling process was developed to examine the economic and environmental benefits of utilizing energy crops for bioenergy products in the northeastern United States. Three energy crops (hybrid willow, switchgrass, and Miscanthus) that can potentially grow on marginal agricultural land or abandoned mine land in the region were considered in the analytical process for the production of biofuels, biopower, and pellet fuel. The supply chain components for the economic analysis and life cycle modeling processes included feedstock establishment, harvest, transportation, storage, preprocessing, conversion, distribution, and final usage of the bioenergy products. Sensitivity analysis was conducted to assess the effects of energy crop yield, transportation distance, conversion rate, facility capacity, and internal rate of return (IRR) on the production of bioenergy products. The required selling price (RSP) ranged from 7.7/GJ to 47.9/GJ for different bioenergy products. The production of biopower had the highest RSP and pellet fuel had the lowest RSP. The results also indicated that bioenergy production using hybrid willow demonstrated lower RSP than the other two perennial grasses. Pellet production had presented the lowest greenhouse gas (GHG) emissions (less than 10 kg CO2 eq per 1000 MJ) and fossil energy consumption (less than 150 MJ per 1000 MJ). The production of biofuel resulted in the highest GHG emissions. Sensitivity analysis indicated that IRR was the most sensitive factor to RSP, followed by conversion rate for biofuel and biopower production. Fuel conversion efficiency and feedstock transport distance had a significant effect on the life cycle environmental impact of the bioenergy products studied. © 2017 Society of Chemical Industry and John Wiley & Sons, Ltd